HDAC9 exacerbates endothelial injury in cerebral ischaemia/reperfusion injury. Issue 6 (10th February 2016) - Shi, Weichen; Wei, Xinbing; Wang, Ziying; Han, Huirong; Fu, Yi; Liu, Jiang; Zhang, Yan; Guo, Jian; Dong, Chuanqiao; Zhou, Di; Zhou, Quan; Chen, Yuxin; et al.
Abstract: Histone deacetylase (HDAC) 9, a member of class II HDACs, regulates a wide variety of normal and abnormal physiological functions, which is usually expressed at high levels in the brain and skeletal muscle. Although studies have highlighted the importance of HDAC‐mediated epigenetic processes in the development of ischaemic stroke and very recent genome‐wide association studies have identified a variant in HDAC9 associated with large‐vessel ischemic stroke, the molecular events by which HDAC9 induces cerebral injury keep unclear. In this study, we found that HDAC9 was up‐regulated in the ischaemic cerebral hemisphere after cerebral ischaemia/reperfusion (I/R) injury in rats and in vivo gene silencing of HDAC9 by recombinated lentivirus infection in the brain reduced cerebral injury in experimental stroke. We further demonstrated that HDAC9 contributed to oxygen‐glucose deprivation‐induced brain microvessel endothelial cell dysfunction as demonstrated by the increased inflammatory responses, cellular apoptosis and endothelial cell permeability dysfunction accompanied by reduced expression of tight‐junction proteins. We further found that HDAC9 suppressed autophagy, which was associated with endothelial dysfunction. This study for the first time provides direct evidence that HDAC9 contributes to endothelial cell injury and demonstrates that HDAC9 is one of critical components of a signal transduction pathway that links cerebral injury to epigenetic modification in the brain.